TRANSLATION QUALITY OF PRETEST - Titis Surgawi; Hermanu Joebagio; Djono Djono (Universitas Sebelas Maret, 2017)
Translation is the process of moving meaning from one language into another language. This research aims to explain the translation quality pretest of students from English into Indonesian. Pretest is the activity to know the student ability before teaching activity are given. This translation quality concern on accuracy, clarity/readibility and acceptability. This research method using qualitative descriptive approach with document analysis technique. The document analyzed is translation pretest on ten student of sixth semester Department of English Teaching Universitas PGRI Madiun. The result of this research shows that 42 data (28%) are high accuracy, 46 data (30,66%) are medium accuracy and 62 data (41,33%) are low accuracy; 47 data (31,33%) are high readibility, 48 data (32%) are medium readibility and 55 data (36,66%) are low readibility; 29 data (19,33%) high acceptability, 42 data (28%) are medium acceptability and 79 data (52,66%) are low acceptability.